Equivalent-resistance based on the analysis of inductor-disconnected discharge behavior for intrinsic safety Buck converters - 刘树林 刘健 李艳 毛鸿 (Journal of coal science & engineering, China, 2008)
An Equivalent-Resistance based Analysis Method （ERAM） was proposed, which can convert the Inductor-Disconnected Discharge （IDD） behavior of the Intrinsically Safe Buck Converter （ISBC） into that of an Equivalent Simple-Inductive-Circuit （ESIC）. According to the inductor disconnected equivalent circuit corresponding to the most dangerous operating case of the converter, the arc discharge time and the variation of output-voltage during the IDD were deduced based on the simple current linear attenuation model. According to the energy equivalence, the equivalent inductor-current of the ESIC was obtained. It is pointed out that although the inductor-current of the Buck converter is much lower than that of the published ignition curve, ignition still occurs and the ignition ability is strengthened with increase of the output capacitance. The proposed analyzing method is verified by the experiment results on IEC standard spark ignition apparatus.